Model-based long-term pricing in maritime container shipping - Jörn Schönberger (Sustainability Management Forum, 2020)
This article reports the development and the assessment of a~freight rate optimization approach based on mathematical modeling and optimization. It exploits the functional interdependency between the price of a~(service) product and the quantity of the product using this price. Solving the proposed model enables a~differentiated and shipper-specific rate determination accompanied by the allocation of the transport capacity provided by the carrier to different shippers. This bilateral pricing between carrier and shippers considers market-based reference rates typically available in the maritime container shipping industry. Herewith, we integrate market-based pricing with demand-based pricing. We validate the proposed model in computational experiments for an artificial pricing scenario. An analysis of the achieved results demonstrates that missing overcapacities will lead to reduced revenues if spot market prices are too low.
Keywords: 650; Environmental Economics; Economics; general; Business and Management; general; Economics; general